Response of four Portuguese grapevine cultivars to infection by Phaeomoniella chlamydospora - SOFIA, Jorge; MOTA, Mariana; GONÇALVES, Maria; REGO, Cecília (Phytopathologia Mediterranea, 2019)
Little is known of the response of Portuguese Dão wine appellation’s most common grapevine cultivars to the causal agents of esca and Petri diseases, despite the high incidence of both diseases in the region and the consequent economic losses. Phaeomoniella chlamydospora has been considered one of the major causal agents of these diseases in that region. The present study evaluated the responses of four of the most propagated Dão’s grapevine cultivars – Alfrocheiro, Aragonez, Jaen and Touriga Nacional – to infection by three different Portuguese isolates of P. chlamydospora. Field trials were conducted in 2012, 2013 and 2015. The cultivar Alfrocheiro was the most susceptible to P. chlamydospora while cv. Jaen was the least. Variation in parameters such as lesion length and pathogen recovery from infected spurs (within trial years) suggest relation of pathogenicity with weather data, particularly temperature. Differences in aggressiveness among isolates were also detected, with one, a non-native, being the most aggressive. These results provide valuable information for local winegrowers, identifying, for the first time, susceptibility differences among local cultivars to P. chlamydospora, and suggesting adjustments to recommended pruning strategies, specifically to leave long spurs and avoid late winter pruning, thus reducing grapevine trunk colonization by P. chlamydospora.